1994
DOI: 10.1002/cne.903410411
|View full text |Cite
|
Sign up to set email alerts
|

Biotin staining in the giant fiber systems of the lobster

Abstract: The avidin-biotin-complex method is a popular immunocytochemical technique. This method labels consistently a group of neurons in the lobster ventral nerve cord in the absence of primary antibodies. The specific staining is due to a relatively high level of endogenous biotin (or biocytin) in these neurons. These biotin-positive neurons are located in the supraesophageal, thoracic, and abdominal ganglia. Intraaxonal injection of Lucifer yellow followed by Texas red-conjugated streptavidin staining reveals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…Biotin labeling has also been reported in cerebellar Purkinje cells, although this was in pigs fed a biotin-supplemented diet (Cooper et al, 1997). These latter results are not easily compared with endogenous biotin in rats maintained on a normal diet, as artificial increases in biotin (as exemplified by ventricular injection of biocytin) leads to widespread labeling of cells that are ordinarily biotin-negative (McDonald et al, 1992;Ma, 1994).…”
Section: Biotin Is Selectively Distributed In Cnsmentioning
confidence: 80%
See 3 more Smart Citations
“…Biotin labeling has also been reported in cerebellar Purkinje cells, although this was in pigs fed a biotin-supplemented diet (Cooper et al, 1997). These latter results are not easily compared with endogenous biotin in rats maintained on a normal diet, as artificial increases in biotin (as exemplified by ventricular injection of biocytin) leads to widespread labeling of cells that are ordinarily biotin-negative (McDonald et al, 1992;Ma, 1994).…”
Section: Biotin Is Selectively Distributed In Cnsmentioning
confidence: 80%
“…Biotin has been identified in the lobster giant axon (Ma, 1994) and in neurosecretory cells of the insect Manduca sexta (Ziegler et al, 1995). Biotin was identified in a subset of neurons from the turtle spinal cord (Berkowitz, 2002), in axons and synaptic boutons in numerous regions of frog brain (Eisner et al, 1996), in salamander and goldfish retina (Bhat- tacharjee et al, 1997), and in two nuclei following song learning in birds (Johnson et al, 2000).…”
Section: Biotin Is Selectively Distributed In Cnsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, McDonald et al (1992) reported that specific sets of neurons in rat brain are stained in histochemical preparations for biotin at an intensity well above background when biocytin (biotinyl-lysine) is injected into the lateral ventricle or brain parenchyma. Ma (1994) documented the selective staining of endogenous biotin or biotin-associated compounds in certain neurons in ganglia of the lobster ventral nerve cord. Although the significance of these effects has not been elucidated, these investigators have suggested that particular neurons may have an elevated requirement for biotin or its derivatives for a specialized function.…”
Section: Indexing Terms: Synapse Olfactory Cortex Nucleus Isthmi Hmentioning
confidence: 99%